A Brontë Reading List: Part 11 — Anne and Emily Brontë. (2nd October 2019) - Ogden, James; Pearson, Sara L.; Cook, Peter
Abstract : The 2016 bicentenary of Charlotte Brontë's birth was marked by an unusually large number of publications on her life and work, including special journal issues of Victorian Review (42.2) and Victorians: A Journal of Culture and Literature (130). In order to accommodate all of this work, we decided to review the year in two parts: the first part (published in July 2019) covered Charlotte Brontë, and this second part covers Anne and Emily Brontë. This list is part of an annotated bibliography of scholarly and critical work. The earlier parts were published in Brontë Studies, 32.2 (July 2007), 33.3 (November 2008), 34.3 (November 2009), 36.4 (November 2011), 37.3 (September 2012), 39.1 (January 2014), 41.3 (September 2016), 42.4 (November 2017), 43.4 (October 2018) and 44.3 (July 2019). The present part covers work published in 2016. Bibliographical details are followed where possible by summaries and assessments. Essays published in Brontë Studies are as a rule excluded, as are books reviewed in Brontë Studies ; readers are directed to the publisher's website, https://www.tandfonline.com, for online access. The author of each entry is indicated by the author's initials in brackets following the entry.